Transforming Your Conference Presentation into a Journal Article - MacDonald, Katya C. (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2021)
In many disciplines, most conference presentations end when the conference does; they do not go on to become peer-reviewed articles. Yet there is also research to suggest that continuing to work with a conference paper to turn it into an article leads to higher research productivity overall, with additional benefits of increasing a researcher's confidence, motivation, and capacity for further research (Lee & Boud, 2003). This article was itself once a conference presentation or, more precisely, a workshop entitled “Transforming Your Conference Paper into a Journal Article” developed for University of Saskatchewan and Saskatchewan Library Association member librarians, and presented to researchers and writers from diverse disciplines. At those presentations attendees asked whether I would be turning this presentation into an article – a very meta question that did indeed seem like a logical next step! Synthesizing multidisciplinary scholarship on academic writing, resources from academic writing coaches, and case studies, this piece is intended to be a DIY workshop focusing on concrete strategies for addressing major barriers in the conference paper-to-article editing process.